Digital Narratives of Religious Contestation: Social Media Responses to Buddhist Monks’ Prayer in a Mosque - Firdian, Farhan; Anam, Haikal Fadhil; Baroroh, Hilma Erfiani (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This study investigates the event of a group of Buddhist monks praying during the Vesak holiday in 2024 at the Baiturrahman Mosque in Bengkal, Temanggung, and the subsequent public responses on social media. In Indonesia, where Islam is the predominant religion, there are sometimes interfaith  encounters that transcend conventional borders. The monks’ prayer, which was recorded and extensively shared on social media sites including Facebook, Instagram, YouTube, and TikTok, provoked a range of responses, from appreciation for religious tolerance to concerns about the sanctity of sacred space. Using mediatization and framing theories, the study explores how the incident was portrayed and how it shaped public perception. A mixed-method approach, combining sentiment and thematic analyses of social media comments, identifies themes of societal harmony, religious identity, and tolerance. Positive sentiments celebrating interfaith tolerance predominated, though some saw it as overstepping religious boundaries. This case highlights social media’s role in framing religious discourse and influencing opinions, emphasizing its impact on interfaith relations and societal tolerance in Indonesia. The study sheds light on how digital media shapes views on interreligious engagement and coexistence.